Comparing the efficacy of repositioning manoeuvres over medications in the treatment of posterior and lateral canal benign paroxysmal positional vertigo: a prospective, randomized and comparative study - Ramalingam, Anbukarasi; Vasanthi L., Agalya Pauline; Ganapathy, Hariharasubramanian (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Benign paroxysmal positional vertigo (BPPV) is a benign peripheral disorder of vestibular system and is the most common cause of peripheral vertigo. The aim of our study was to compare and assess the efficacy of Epley’s and Barbeque roll over manoeuvres with labyrinthine sedatives in the management of Benign Paroxysmal Positional Vertigo (BPPV) over a period of one month and to know the prevalence of BPPV in different age and gender groups among the two semicircular canals(posterior and lateral). Methods-This prospective randomized comparative clinical trial included 60 patients with clinically diagnosed BPPV in a tertiary care centre and were investigated for a period on one year. The clinical diagnosis of specific canal type of BPPV was assessed based on the diagnostic tests, Dix Hallpike test and McClure test. In manoeuvre group, posterior canal BPPV, Epley’s manoeuvre was performed and for lateral canal BPPV, Barbeque roll over manoeuvre was performed as treatment. In pharmacological group, labyrinthine sedatives i.e. either cinnarizine 25mg twice a day or betahistine 16 mg twice a day were administered for one month as treatment. Results: Results were assessed at the end of 48 hours (immediate time period) and at four weeks’ time period after the treatment, under three different outcome categories namely disappeared, improving and unchanged. Treatment of Benign Paroxysmal Positional Vertigo with repositioning manoeuvre had higher success percentage of 83.3% than the medical treatment. Conclusion: The treatment of BPPV with repostioning manoeuvres had a better outcome than the medical treatment.